Determinants of Hypertension Stage Among Patients in a Primary Health Care Center: A Cross-Sectional Study - Indana Maslakhah; Heny Nurmayunita; Yuni Asri (CV. Devitara, 2025)
Hypertension remains a major public health problem worldwide and is associated with increased risk of cardiovascular complications. Identifying factors associated with the stage of hypertension is important for improving disease management at the primary health care level. This study aimed to identify determinants associated with the stage of hypertension among patients in a primary health care center. A cross-sectional study was conducted at Libano Primary Health Care Center, Morotai Island, Indonesia, in December 2025. A total of 30 hypertensive patients were included in the study. Data on demographic characteristics, clinical factors, and lifestyle behaviors were collected from patient records. Descriptive statistics were used to summarize the data, and bivariate analysis was performed using the Chi-square test or Fisher’s exact test when appropriate. Statistical analysis was conducted using SPSS version 26, with a significance level set at p < 0.05. The distribution of hypertension stages was equal, with 50.0% classified as Stage 1 and 50.0% as Stage 2 hypertension. Medication adherence was significantly associated with the stage of hypertension (p = 0.017). Patients who adhered to antihypertensive medication were more likely to have Stage 1 hypertension, while non-adherent patients were more frequently classified as Stage 2. Other variables, including age, gender, educational level, employment status, family history of hypertension, smoking status, dietary pattern, and physical activity, were not significantly associated with hypertension stage. Medication adherence was the main determinant associated with the stage of hypertension. Strengthening adherence to antihypertensive therapy may help prevent the progression of hypertension.